(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: Happiness is a crucial component of human lives. It is thus logical to assume that considering satisfaction and joy will produce profitable outcomes. The study intended to examine the effectiveness of interaction with children on happiness among the elderly. Methods: We chose 20 institutionalized elderly and assigned them randomly to experimental and control groups. We used the happiness rating scale to test the happiness levels among the elderly. We chose children for interaction based on their attitudes towards the elderly. Then the experimental group elderly interacted with the children twice a week for four weeks. Results: The paired ‘t’ test calculated for the experimental (P value= < 0.001) and control group (P value= 0.472) implied that the interaction with children is useful to enhance elderly happiness. Conclusion: We thus recommend that the educational curriculum include the children’s visit to the elderly homes. Also, establishing children’s homes and the elderly homes under one roof can benefit either group. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 318-322